Pengembangan Media Promosi Furniture Berbasis Augmented Reality Menggunakan Multimedia Development Life Cycle - Fatimah, Dini Destiani Siti; Supriatna, Asep Deddy; Gotawa, Ikhsanudin (Jurnal Algoritma, 2024)
Augmented Reality (AR) is an interactive and innovative online promotional media that provides interesting new experiences for consumers. In the furniture industry, AR technology can be used to make it easier for consumers to choose products and reduce the risk of purchasing errors. This research aims to implement Augmented Reality technology in web-based promotional media for furniture products using the Multimedia Development Life Cycle method. This method is used to help develop effective and efficient AR web applications. This research is important because effective promotional media can influence consumer purchasing decisions. The expected final result is a promotional media for furniture products that applies the Augmented Reality (AR) feature in its promotional media.